Effect of procathepsin D activation peptide on gene expression of breast cancer cells - Beneš, Petr; Vashishta, Aruna; Saraswat, Ohri Sujata; Fusek, Martin; Pospíšilová, Šárka; Tichý, Boris; Větvička, Václav (Cancer letters, 2006)
Overexpression of procathepsin D (pCD) is reported to occur in numerous types of cancer and is associated with increased growth and metastasis. It has been established that pCD affects multiple stages of tumor progression including proliferation, angiogenesis and metastasis. Previously, we showed that the mitogenic effect of pCD on cancer cells is mediated by interaction of its activation peptide (AP) with yet unidentified cell surface receptor. In this investigation, gene expression profiles were compared between AP-treated and control human breast cancer ZR-75-1 cells to elucidate the mechanism of AP mitogenicity. Several differentially expressed genes involved in signal transduction, regulation of cell cycle, apoptosis, tumor invasion and metastasis were identified using microarray technology. These findings, including overexpression of NF-kappaB2, were confirmed in breast cancer cell lines by reverse-transcriptase PCR (RT-PCR). Understanding the mechanism of pCDs effect on breast cancer cells could extend possibilities of breast cancer treatment in the future.
Keywords: signální transdukce; Signal Transduction; regulace genové exprese u nádorů; nádorové proteiny; Humans; Tumor Cells, Cultured; prekurzory enzymů; Cathepsin D; Oligonucleotide Array Sequence Analysis; polymerázová řetězová reakce s reverzní transkripcí; financování organizované; NF-kappa B - podjednotka p52; Financing, Organized; lidé; Reverse Transcriptase Polymerase Chain Reaction; nádorové buňky kultivované; Peptide Fragments; Breast Neoplasms; kathepsin D; stanovení celkové genové exprese; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; peptidové fragmenty; nádory prsu; NF-kappa B p52 Subunit; Gene Expression Profiling; Neoplasm Proteins; Gene Expression Regulation, Neoplastic; Enzyme Precursors